THE EFFECT OF SEX ON THE ACCURACY OF PREDICTING CARCASS COMPOSITION OF ROSS BROILER CHICKENS - T. M. Shafey; M. A. Alodan; E.O.S. Hussein; H.A. Al-Batshan (Journal of Animal and Plant Sciences, 2013)
Linear regression equations predicting carcass composition by live body weight were developed using data from 40 males (M) and 40 females (F) of Ross broiler chickens at 33 days of age. Equations from M, F and combined sexes (M+F) were compared to examine the effects of sex on the precision of predicting carcass composition. M birds had higher live body weights and weights of carcasses, drumsticks and wings than F birds. Live body weight was positively correlated with all the carcass components in M and M+F (r=0.98 to 0.26) and all carcass components except abdominal fat in F birds (r=0.99 to 0.46). Prediction equations for carcass weight and carcass composition of breast, drumsticks, thighs, back and wings of F birds were slightly more variable in precision (R2=98.3 to 21.2%) than those developed in Mbirds (R2=96.9 to 63.4%), and equations developed from M + F birds were intermediate. Sex of bird significantly influenced the R 2 when predicting neck and wings weights. It can be concluded that prediction equations developed fromlive body weight can be useful to estimate carcass composition. Equations identified differences between sexes in predicting weights of wings and neck in the carcass of Ross broiler chickens.
Keywords: Broiler; Chicken; Carcass components; Regression equations